2011
DOI: 10.1088/0957-4484/22/27/275714
|View full text |Cite
|
Sign up to set email alerts
|

Comparing carbon nanotubes and graphene nanoplatelets as reinforcements in polyamide 12 composites

Abstract: We investigate the influence of nanofillers including carbon nanotubes (CNTs) and graphene nanoplatelets on a thermoplastic engineering polymer, polyamide 12 (PA12). The comparison between these two important nanofillers as to how they influence the structure and properties of the polymer is systematically studied. The polymer-nanofiller composites were prepared using a twin-screw micro-extruder and the composite was thereafter hot pressed into thin films. The structure (using wide angle x-ray diffraction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
86
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 41 publications
13
86
2
Order By: Relevance
“…In general for polymeric nanocomposites, few reports have investigated the mechanical properties of 2D carbon or inorganic nanostructures 4549 compared to carbon nanotubes. 2, 3, 5, 15, 22, 24, 50, 51 Song et al reported ≈ 74% increase in the Young’s modulus of polypropylene composites compared to pristine polymer composite controls at 0.42 vol% loading of exfoliated graphene platelets.…”
Section: Resultsmentioning
confidence: 99%
“…In general for polymeric nanocomposites, few reports have investigated the mechanical properties of 2D carbon or inorganic nanostructures 4549 compared to carbon nanotubes. 2, 3, 5, 15, 22, 24, 50, 51 Song et al reported ≈ 74% increase in the Young’s modulus of polypropylene composites compared to pristine polymer composite controls at 0.42 vol% loading of exfoliated graphene platelets.…”
Section: Resultsmentioning
confidence: 99%
“…The GnP were physically premixed with a surfactant powder and pestled for 30 min before compounding with PA12 by using a micro extruder. The adding of 0.5 wt.-% GnP leads to an improvement in the yield strength by 32.2 % relative to the yield strength of 36.7 MPa for pure PA12 [7]. Also Zhao et al observe a large effect on the mechanical properties of polyvinyl alcohol (PVA) at low loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide offers good thermal stability, chemical resistance and excellent frictional properties. 1,2 However, the application of neat PA6 or PA66, two kinds of nylon, has been limited to some special fields due to its relatively low thermal conductivity. Therefore, PA is mostly compounded with other polymers [3][4][5] or rigid particles [6][7][8][9][10][11][12][13] to overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%